Exploring the Relationship Between Reward Systems and English Learning Motivation: A Mixed-Methods Approach in an Indonesian Islamic High School - Maizari Maizari; Sumarni Sumarni; Dewi Novita (Universitas Muhammadiyah Barru, 2024)
This study aimed to explore the impact of rewards on students' motivation to learn English, framed within an extrinsic motivation theoretical perspective. A mixed-methods research design was employed, combining quantitative data from questionnaires with qualitative insights from interviews. The sample consisted of 20 eleventh-grade students from one of the Islamic High School at MAS Al Mustaqim in Kubu Raya, selected through purposive sampling, with 5 students also participating in in-depth interviews. Quantitative analysis revealed that 75% of students strongly agreed that rewards such as praise and gifts significantly increased their motivation, with teacher influence being particularly impactful. Additionally, 75% of students agreed that receiving stationery as a reward for correct answers further enhanced their motivation. Interview data supported these findings, highlighting positive perceptions of rewards and increased enthusiasm for learning. The study concludes that extrinsic rewards can effectively boost students' motivation to learn English.